2012
DOI: 10.1071/is12026
|View full text |Cite
|
Sign up to set email alerts
|

Challenging species delimitation in Collembola: cryptic diversity among common springtails unveiled by DNA barcoding

Abstract: Collembola is one of the major functional groups in soil as well as a model taxon in numerous disciplines. Therefore the accurate identification of specimens is critical, but could be jeopardised by cases of cryptic diversity. Several populations of six well characterised species of springtails were sequenced using the COI barcode fragment as a contribution to the global Collembola barcoding campaign. Each species showed high intraspecific divergence, comparable to interspecific sequence divergence values obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 41 publications
8
72
0
Order By: Relevance
“…Even for species that had been barcoded at other sites, their sequences were different from those collected from identical morphological species at the study site (i.e., <90% of sequence similarity). These results support the huge and hidden diversity in Collembola shown in previous studies (e.g., Porco et al 2012aPorco et al , 2012bCicconardi et al 2013) and suggest the need for generating more reference sequences of this group, more extensively at our study site as well as in various other geographic regions. At present, the construction of a locally collected database for mtCOI and mt16S genes will be needed to identify collembolan species from metabarcoding data.…”
Section: Selectivity and Sensitivity Assessed Using Natural Communitysupporting
confidence: 76%
See 2 more Smart Citations
“…Even for species that had been barcoded at other sites, their sequences were different from those collected from identical morphological species at the study site (i.e., <90% of sequence similarity). These results support the huge and hidden diversity in Collembola shown in previous studies (e.g., Porco et al 2012aPorco et al , 2012bCicconardi et al 2013) and suggest the need for generating more reference sequences of this group, more extensively at our study site as well as in various other geographic regions. At present, the construction of a locally collected database for mtCOI and mt16S genes will be needed to identify collembolan species from metabarcoding data.…”
Section: Selectivity and Sensitivity Assessed Using Natural Communitysupporting
confidence: 76%
“…While >3% of difference in COI sequence (i.e., <97% of identity) has been usually considered to indicate distinct species in various taxa (Hebert et al 2003), greater than 3% difference within morphological species has been previously reported in Collembola (e.g., Porco et al 2012aPorco et al , 2014Anslan and Tedersoo 2015) and was found in the present study. As distributions of inter-and intraspecific sequence similarities overlapped (Fig.…”
Section: Selectivity and Sensitivity Assessed Using Natural Communitysupporting
confidence: 52%
See 1 more Smart Citation
“…Mostly, the aim has been to characterize the diversity of an assemblage and identify alien species among its members in a given recipient area, or to verify whether given populations are from species thought to be nonindigenous (e.g. Scheffer et al 2006;Smith and Fisher 2009;Porco et al 2012Porco et al , 2013Fern andezAlvarez and Machordom 2013;Zhang et al 2013a). Such approaches nonetheless are subject to the same kinds of problems as those facing DNA barcoding generally (see review by Taylor and Harris 2012).…”
Section: The Initial Stages -Entrainment Risk and Transportmentioning
confidence: 99%
“…The amplified products showed approximately 700bp ( Figure 2). Several studies have been reported that sequence diversity in a ~650 bp region near the 5' end of the MT-COI gene provides strong species-level resolution for varied animal groups, including birds [1,12], fishes [7,30], springtails [5,24], spiders [5,6] and moths [16,20]. It has been reported that the primer pair, (LCO_MT1_NC101214 and LCO_MT2_NC021214) was not so ''universal'' as thought before, as it would still fail to amplify some taxa [21,28].…”
Section: Parapenaeopsis Sculptillismentioning
confidence: 99%